2020
DOI: 10.1055/s-0040-1719030
|View full text |Cite
|
Sign up to set email alerts
|

Exome Sequencing Identifies Abnormalities in Glycosylation and ANKRD36C in Patients with Immune-Mediated Thrombotic Thrombocytopenic Purpura

Abstract: Background Immune-mediated thrombotic thrombocytopenic purpura (iTTP) is a potentially fatal blood disorder, resulting from autoantibodies against ADAMTS13 (a disintegrin and metalloproteinase with a thrombospondin type 1 motif, member 13). However, the mechanism underlying anti-ADAMTS13 autoantibody formation is not known, nor it is known how genetic aberrations contribute to the pathogenesis of iTTP. Methods Here we performed whole exome sequencing (WES) of DNA samples from 40 adult patients with i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 57 publications
(55 reference statements)
0
4
0
Order By: Relevance
“…[38] Variations in the ANKRD gene family, particularly ANKRD36C and its paralogs, are more prevalent in immune-mediated thrombotic thrombocytopenic purpura (iTTP) than in healthy controls. [39] Our study showed that the expression of ANKRD36 was significantly higher in DKD samples than in normal samples. Considering that DKD is a risk factor for hypertension, [40] we would like to explore whether ANKRD36 regulates YY1 in future studies.…”
Section: Journal Of Translational Internal Medicine / Aopmentioning
confidence: 53%
“…[38] Variations in the ANKRD gene family, particularly ANKRD36C and its paralogs, are more prevalent in immune-mediated thrombotic thrombocytopenic purpura (iTTP) than in healthy controls. [39] Our study showed that the expression of ANKRD36 was significantly higher in DKD samples than in normal samples. Considering that DKD is a risk factor for hypertension, [40] we would like to explore whether ANKRD36 regulates YY1 in future studies.…”
Section: Journal Of Translational Internal Medicine / Aopmentioning
confidence: 53%
“…[ 38 ] Variations in the ANKRD gene family, particularly ANKRD36 C and its paralogs, are more prevalent in immune-mediated thrombotic thrombocytopenic purpura (iTTP) than in healthy controls. [ 39 ] Our study showed that the expression of ANKRD36 was significantly higher in DKD samples than in normal samples. Considering that DKD is a risk factor for hypertension,[40] we would like to explore whether ANKRD36 regulates YY1 in future studies.…”
Section: Discussionmentioning
confidence: 72%
“…In 2020, we introduced optional “Visual Summaries” to convey the main message of the manuscript in a clear and concise graphic manner so that readers can grasp its contents and relevance at a glance. In the past two years, we have received an increasing number of such graphical abstracts which greatly improved the reading quality of the articles published 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 some of which have even been selected for the T&H Issue Cover 4 5 11 15 33 38 ( Fig. 2 ).…”
Section: What's New?mentioning
confidence: 99%